Pengembangan Bahan Ajar Matakuliah Dayung Berbasis Blended Learning untuk Mahasiswa PJKR - Damaris Marlissa; Wasis Djoko Dwiyogo; Supriyadi Supriyadi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: The purpose of this research and development is to create a teaching material creation based on blended learning (face to face, offline, and online) for rowing teaching materials. The development of teaching materials for the blended learning-based rowing course, the researchers used a research method based on blended learning for problem-solving learning outcomes. The researcher obtained the results from the effectiveness test at the three meetings the researcher had conducted. Effectiveness test data: in the first meeting: the average grade grade of students obtained the letter A (89.63%). The second meeting: the average grade grade of the students was obtained by the letter A (90.38%). In the third meeting: the average grade score of the students was obtained "A" (91.63%). The Efficiency Test of the first meeting obtained the total time for studying and working on the questions: 1) the longest total time was 1 hour 16 minutes 17 seconds and the fastest time was 1 hour 02 minutes 21 seconds. Second meeting: the longest time is 1 hour 11 minutes 41 seconds and the fastest time is 1 hour 26 seconds. The third meeting: the longest time is 1 hour 09 minutes 27 seconds and the fastest time is 1 hour 44 seconds. The results of the engagement quality test were obtained from a survey that circulated at 3 meetings to test the adequacy of the quantity of tools: (1) 5 items for the main meeting (face to face), (2) 7 objects for the next meeting (disconnected), (3) ) 5 things for the third meeting (online) focus and from these results indicate securing the level of attractiveness of the supporting material enhancement items for the mixed learning-based rowing course: (1) 89.75% collection I (close and personal), (2) 90 , 4% meeting II (disconnected), (3) 91.125% collection III (on the web) with very substantial rules.Abstrak: Tujuan penelitian dan pengembangan ini yaitu untuk menciptakan sebuah kreasi bahan ajar berbasis blended learning (tatap muka, offline, dan online) bagi bahan ajar dayung. Pengembangan bahan ajar matakuliah dayung berbasis blended learning ini peneliti memakai metode penelitian berbasis blended learning untuk hasil belajar pemecahan masalah. Peneliti memperoleh hasil dari uji efektivitas  pada tiga kali pertemuan yang telah peneliti lakukan. Data uji efektivitas: pada petemuan pertama: rata-rata nilai kelas mahasiswa diperoleh angka huruf A (89,63%). Pertemuan kedua: rata-rata nilai kelas mahasiswa diperoleh angka huruf A (90,38%). Pada petemuan ketiga: rata-rata nilai kelas mahasiswa diperoleh “A” (91,63%). Uji Efisiensi petemuan pertama diperoleh total waktu belajar dan mengerjakan soal: 1) total waktu terlama 1 jam 16 menit 17 detik dan waktu tercepat 1 jam 02 menit 21 detik. Pertemuan kedua: waktu terlama 1 jam 11 menit 41 detik dan waktu tercepat 1 jam 26 detik. Pertemuan ketiga: waktu terlama 1 jam 09 menit 27 detik dan waktu tercepat 1 jam 44 detik. Hasil uji kualitas keterikatan didapatkan dari survei yang beredar pada tiga pertemuan untuk menguji kecukupan dengan kuantitas alat (1) lima soal untuk pertemuan utama (tatap muka), (2) 7 soal untuk pertemuan berikutnya (terputus), (3) lima soal untuk pertemuan ketiga (online) fokus dan dari hasil ini menunjukkan pengamanan tingkat daya tarik dari item peningkatan bahan pendukung untuk kursus mendayung pembelajaran campuran berbasis: ( 1) 89,75% pengumpulan I (tatap muka), (2) 90,4% pertemuan II (offline), (3) 91,125% pengumpulan III (online) dengan aturan yang sangat substansial.